Effect of high volume fly ash and micro-steel fiber on flexural toughness and durability properties in self-compacting lightweight mortar (SCLM) - Memi̇ş, Selçuk; Bayraktar, Oğuzhan Yavuz; Kaplan, Gökhan (Elsevier BV, 2021)
Abstract In this study, high volumes of fly ash and micro-steel fiber were used to improve lightweight aggregate mixes' strength and durability properties that can be used in the prefabrication industry. The developed composite can be used in roof truss flooring of steel structures and bridge decks. Although the unit weight of the mixtures was reduced below 2000 kg/m3, micro steel fibers were used to improve the behaviour against seismic effects. The increase in fly ash content increased the porosity, water absorption, and water penetration depths of the mixes. The increase in the steel fiber content created a micro-filter effect, reducing the water absorption and water penetration depths. The hardened unit weights of the mixes vary between 1305–1723 kg/m3, while their 91-day compressive strength varies between 30.9 and 46.4 MPa. It has been observed that the mixes using steel fiber are in the medium and good class in the residual strength factors specified in ASTM C 1018. The carbonation depth of the mixes using 50% fly ash increased more than 5.5 times compared to the reference mix. After the freeze–thaw effect, spills occurred on the surfaces of the mixes due to fiber corrosion.
Keywords: 13. Climate action; 12. Responsible consumption